Patient’s Knowledge Assessment on Diabetes and SelfCare Practices Among Older Adolescents with Type 1 Diabetes Mellitus in Malawi - Etta Chimbe Phiri; Gladys Msiska; Lucy Ida Kululanga; Balwani Chingatichifwe Mbakaya (European Scientific Journal, ESJ, 2017)
Adolescents with Type 1 Diabetes Mellitus (T1DM) face risks of long-term health complications due to difficulties in achieving and maintaining target glycemic control. The study aimed at assessing knowledge on diabetes and self-care practices among older adolescents with type 1 diabetes to identify significant knowledge gaps. Gathering information from adolescents on how much they know about the condition and their self-care practices would help identify significant knowledge and self-care gaps. A quantitative descriptive cross-sectional study design was used. Convenience sampling was employed to recruit 46 adolescents with TIDM from two tertiary hospitals in Malawi. Data were collected using interviewer administered questionnaire from January to March, 2014, and analyzed using SPSS version 20. The study results revealed inadequate knowledge amongst the adolescents on issues pertinent to self-cares. 58% (42/72) had inadequate knowledge on managing hyperglycemia, 61% (28/46) were inappropriately doing the self-monitoring of blood glucose resulting in high admission rate with 44% being admitted 3-4 times and 11% more than 7 times in a year. Linear regression showed a significant association between age and number of admissions (P=0.022) hence as age increases, so does the number of admissions. 78% (36/46) were not adequately counseled on diet plan. Excessive thirst and frequent urination were the most mentioned signs of Type 1 Diabetes Mellitus 24% (45/191). Ulcers on the feet were the most mentioned complication 33% (42/127. Majority of the adolescents (70%, 32/46) knew why changing insulin injection site is important. The study identified a significant need to develop relevant health education materials on diabetes and self-care practices for adolescents within Malawi to help them manage the condition hence averting long term complications.